State reform, decentralization and subnational public enterprises. The case of the province of Río Negro, Argentina (National Administration Journal, 2023)
The aim of this paper is to analyze the impact of state reform and the decentralization process at the federal level in Argentina during the 1990s on the current conformation of the public business sector at the provincial level. To this end, a case study focused on the province of Río Negro is carried out, appealing to primary and secondary sources, with a view to identifying this incidence in the origin of the entities that compose it at present. The results of the analysis allow us to consider a significant incidence of state reforms and decentralization policies in the creation of a relevant part of the public enterprises in Río Negro.
Keywords: Public companies; state; public administration; Argentina